Characterisation of a new mouse monoclonal antibody (ONS-M21) reactive with both medulloblastomas and gliomas. - Moriuchi, S. (Nature Publishing Group, 1993)
We developed an IgG1 mouse monoclonal antibody (ONS-M21) directed against a cell surface antigen of medulloblastomas and gliomas in immunisation of mice with the ONS-76 medulloblastoma cell line. The antibody specifically reacted with medulloblastomas, supratentorial primitive neuroectodermal tumours (SPNETs) and gliomas, but not with other neuroectodermally derived tumours (neuroblastoma and melanoma) or with other kinds of tumours (meningioma, neurinoma, leukaemia, and small cell lung cancer). No reactivity was identified with normal body tissues, including peripheral blood cells. Characterisation of the ONS-M21 antigen showed that it was a trypsin-sensitive glycoprotein with a molecular weight of 80 kDa on SDS-PAGE. The pattern of reactivity and the biochemical properties of this antigen were different from those of other markers of medulloblastoma. These results indicate that ONS-M21 detects a new tumour-associated cell surface antigen specifically expressed by medulloblastomas, SPNETs, and gliomas. This is the first report that medulloblastomas may share common cell surface antigens with gliomas, although most studies have concluded that medulloblastoma has a predominantly neuronal phenotype. The lack of reactivity with normal tissue implies that ONS-M21 has potential applications as both a diagnostic tool and a therapeutic agent. IMAGES: